A Research-Based Approach to Game Writing Pedagogy - Hudson, Seth (Transactions of the Digital Games Research Association, 2021)
This paper discusses the importance of, and presents a possible framework for, phenomenological research of game industry practice to enhance pedagogy in computer game design (CGD) education. Built around examples from one such study on the practices of game industry writers, the author provides background for the study in question, outlines the theoretical framework of the research design, and presents an overview of the findings. A discussion of possible impacts and further applications in other subdisciplines of game development follows.